2020
DOI: 10.1364/boe.391028
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive investigation of adipose tissue by time domain diffuse optical spectroscopy

Abstract: The human abdominal region is very heterogeneous and stratified with subcutaneous adipose tissue (SAT) being one of the primary layers. Monitoring this tissue is crucial for diagnostic purposes and to estimate the effects of interventions like caloric restriction or bariatric surgery. However, the layered nature of the abdomen poses a major problem in monitoring the SAT in a non-invasive way by diffuse optics. In this work, we examine the possibility of using multi-distance broadband time domain diffuse optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
1
10
0
1
Order By: Relevance
“…For example, Spilenlli 37 et al studies the optical properties of breast tissue and discovered a positive correlation between BMI and lipid and total hemoglobin, and a negative correlation between BMI and water content. When studying the optical properties of adipose tissue, Lanka 38 et al results show that obese have lesser values for absorption and reduced scattering coefficients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Spilenlli 37 et al studies the optical properties of breast tissue and discovered a positive correlation between BMI and lipid and total hemoglobin, and a negative correlation between BMI and water content. When studying the optical properties of adipose tissue, Lanka 38 et al results show that obese have lesser values for absorption and reduced scattering coefficients.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that obesity creates variations in skin physiology 5 , 35 38 . These changes include but are not limited to skin barrier function, epidermal changes, dermal changes, and changes to the vascular and capillary recruitment function.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are no digital biomarkers known for these markers, although early developments are being made for wearable measurement of cholesterol ( 82 ). In addition, intra-abdominal fat spectroscopy, associated with lipid regulation and inflammation, is likely to become possible in the near future ( 83 ). Other than that, the autonomic imbalance is associated with metabolic syndrome and its components, including cholesterol and triglycerides ( 84 , 85 ), indicating that heart rate variability may serve as an indirect reflection of lipid dysregulation.…”
Section: Digital Resilience Biomarkersmentioning
confidence: 99%
“…With all these developments, POLIMI has been a major contributor to multispectral TD-NIRS and were able to characterize various tissue over a large bandwidth. They were able to characterize bones [47][48][49], thyroid tissues [50], adipose tissues [51], collagen [46,52], and elastin [53]. This groundwork was crucial in order to investigate the tissue composition of breast for example, which can help for diagnosis of cancerous tissue [54,55].…”
Section: Novel Instrument Developementmentioning
confidence: 99%